2001
DOI: 10.1053/ejso.2001.1169
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid tumours

Abstract: Desmoid tumours exhibit fibroblastic proliferation and arise from fascial or musculoaponeurotic structures. Despite their benign microscopic appearance, and their negligible metastatic potential, the propensity of desmoid tumours for local infiltration is potentially significant in terms of deformity, morbidity and mortality due to pressure effects and obstruction of vital structures and organs. The rarity of desmoid tumours, coupled with the variability in their clinical course, renders these lesions a vexing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
271
0
24

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(300 citation statements)
references
References 63 publications
5
271
0
24
Order By: Relevance
“…Desmoid tumours are most common between puberty and 40 years of age with a peak incidence between the ages of 25-35 years. Women are more commonly affected than men [11,19,21,24]. In our study, the mean age at diagnosis was 32 years, and men outnumbered the women.…”
Section: Discussionmentioning
confidence: 47%
“…Desmoid tumours are most common between puberty and 40 years of age with a peak incidence between the ages of 25-35 years. Women are more commonly affected than men [11,19,21,24]. In our study, the mean age at diagnosis was 32 years, and men outnumbered the women.…”
Section: Discussionmentioning
confidence: 47%
“…Female hormones and trauma including surgical scars are reportedly associated with occurrence of desmoid tumors [1]. Although surgical resection is indicated if the tumor enlarges, the recurrence rate is high at 19% -39.3% [1]- [3], and follow-up is often adopted as the treatment of first choice [4].…”
Section: Discussionmentioning
confidence: 99%
“…This disease is diagnosed by not only imaging studies like CT scan or MRI but histological examinations such as biopsy It often occurs in the trunk and extremities, and surgical resection is indicated if the tumor grows. The recurrence rate is high at 19% -39.3% [1]- [3], and follow-up is often selected as the first choice [4]. We report a patient with a desmoid tumor which had gradually grown in the left lower abdominal port site 1 year after post-chemotherapy laparoscopic RPLND for metastatic testicular tumor; the tumor is diagnosed as desmoid tumor.…”
Section: Introductionmentioning
confidence: 97%
“…Symptoms depend on the location of the tumor. Many studies have shown that between 37% and 50% of desmoids arise in the abdominal region 6 . Intra-abdominal desmoids can remain asymptomatic for a considerable period, while relentlessly enlarging and infiltrating adjacent structures causing intestinal, vascular and urinary obstruction or neural involvement 7 .…”
Section: Discussionmentioning
confidence: 99%